1999
DOI: 10.1097/00000542-199904000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Modeling of M6G Formation after Oral Administration of Morphine in Healthy Volunteers 

Abstract: M6G may contribute to the analgesic and side effects seen with long-term morphine treatment. The current model of morphine and M6G pharmacokinetics after oral administration of morphine may serve as a pharmacokinetic basis for experiments evaluating the analgesic contribution of M6G with long-term oral dosing of morphine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 39 publications
2
31
0
1
Order By: Relevance
“…A two-compartment model has already been used to describe the pharmacokinetic of orally administered morphine, whereas data for intravenously administered morphine are sometimes better described by a three-compartment model [28,29]. The good correlation between the predicted population and observed morphine concentrations and the satisfactorily prediction-corrected VPCs indicate that our model is valid.…”
Section: Discussionmentioning
confidence: 80%
“…A two-compartment model has already been used to describe the pharmacokinetic of orally administered morphine, whereas data for intravenously administered morphine are sometimes better described by a three-compartment model [28,29]. The good correlation between the predicted population and observed morphine concentrations and the satisfactorily prediction-corrected VPCs indicate that our model is valid.…”
Section: Discussionmentioning
confidence: 80%
“…6,126,132,133 It has been reported that glucuronides can be deconjugated after they have been excreted through the bile to the gut lumen, 10 however the major route of elimination of M6G is thought to be excretion via the kidney. 9,[134][135][136][137] Consistent with this is the observation that M6G accumulates in patients with renal impairment. 7,113,138 -142 As noted previously, in man morphine, unlike M6G, undergoes metabolism, chiefly to M3G and M6G but other minor metabolites include morphine-3,6-diglucuronide, morphine-3-ethereal sulphate, normorphine, normorphine-6-glucuronide, normorphine-3-glucuronide, and codeine.…”
Section: B Metabolism and Excretionmentioning
confidence: 84%
“…Study medication consisted of oxymorphone ER tablets (20 mg) (Endo Pharmaceuticals, Chadds Ford, Pa.), morphine sulfate CR tablets (15,30, 60, 100 mg) (MS Contin, Purdue Pharma L.P., Stamford, Ct.), and oxycodone hydrochloride tablets (20, 40, 80 mg) (OxyContin, Purdue Pharma L.P.), which were administered orally every 12 h. Respective rescue medications for breakthrough pain were IR tablet formulations of oxymorphone (5 mg), morphine (15, 30 mg), or oxycodone (5 mg). No other opioids were used during the study period.…”
Section: Study Proceduresmentioning
confidence: 99%
“…Based on the parenteral equianalgesic ratio [13] and oral bioavailability [30] of morphine CR or oxycodone CR [11] to oxymorphone ER, it was estimated that patients should be converted from morphine CR to oxymorphone ER at a ratio of 3:1 and from oxycodone CR to oxymorphone ER at a ratio of 2:1 [14]. Patients were started on half the converted dose to allow appropriate titration.…”
Section: Study Proceduresmentioning
confidence: 99%